Informal Practices of Localizing Open Educational Resources in Ghana - Bradshaw, Emily Durham; McDonald, Jason K. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Research on the use of open educational resources (OER) has often noted the potential benefits for users to revise, reuse, and remix OER to localize it for specific learners. However, a gap in the literature exists in terms of research that explores how this localization occurs in practice. This is a significant gap, given the current flow of OER from higher-income countries in the Global North to lower-income countries in the Global South. This study explored how OER from one area of the world was localized when used in a different cultural context. Interviews from six facilitators of an OER human rights course in Ghana showed that without initial awareness of OER, localization happened largely informally. Practices included (a) technological workarounds and persistence; (b) spontaneous language translation; (c) cultural recontextualization through spontaneous adjustment, content substitutions, and discussion; and (d) social responsiveness. We found implications for designers to anticipate challenges related to dependence on technology, intentionally leave space for informal localization, and allow for linguistic flexibility.